Analysis of the current status of cognitive-behavioral therapy for insomnia based on bibliometrics - LU Tianyou, ZHENG Tingwei, XING Jibin, CHENG Nan, ZHOU Shaoli (Xin yixue)
Objective To summarize the research progress and hotspots of cognitive behavioral therapy for insomnia and predict future research directions in this field. Methods Literature related to cognitive behavioral therapy for insomnia was retrieved from the Web of Science Core Collection （WoSCC） database from 2003 to 2024. VOSviewer and CiteSpace software were used for bibliometric visual analysis. Results A total of 3，256 articles from 3，254 institutions in 77 countries were included， primarily from the USA and China. Since 2017， research in this field has entered a rapid development phase. The journal with the highest publication volume on cognitive behavioral therapy for insomnia is Sleep， which is also the most cited journal， with a total of 13，349 authors contributing to these papers； “sleep quality”“acupuncture treatment”“mental health”“novel coronavirus pneumonia”“pregnancy”“quality of life”are current research hotspots and trends in this field. Conclusion Over the past 21 years， cognitive behavioral therapy for insomnia has developed rapidly， and future trends and research hotspots in this field may focus on “acupuncture treatment” and “mental health”.